CYP2D6 haplotypes with enhancer single-nucleotide polymorphism rs5758550 and rs16947 (*2 allele): implications for CYP2D6 genotyping panels. Issue 2 (February 2019) - Ray, Balmiki; Ozcagli, Eren; Sadee, Wolfgang; Wang, Danxin
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: CYP2D6 metabolizes ∼25% of all clinically used drugs, with numerous genetic polymorphisms affecting enzyme activity and drug response. Clinical utility of current CYP2D6 genotyping is partially compromised the unresolved complex haplotype structure of the CYP2D6 locus. We have identified a distal enhancer single-nucleotide polymorphism rs5758550 that robustly increases CYP2D6 expression, whereas rs16947 ( CYP2D6*2 ), previously considered inert, reduces correct mRNA splicing and expression, thereby affecting presumed activity of other alleles on the *2 haplotype. Objective: This study aims to determine the structure and frequency of haplotypes containing either rs5758550 or rs16947, or both, together with other relevant CYP2D6 alleles, assigning predictive enzyme activity scores to each, and addressing ambiguities in estimating diplotypes in different populations. Methods: The structure and frequency of haplotypes containing rs5758550 and/or rs16947 in different populations were determined by using phased genotype data from 'The 1000 Genomes Project'. The assigned haplotype–phenotype relationship was tested by associating assigned CYP2D6 activity score with CYP2D6 enzyme activity in a cohort of 122 human liver microsomes. Results: Addition of enhancer single-nucleotide polymorphism rs5758550 and *2 to a CYP2D6 panel improves prediction of CYP2D6 activity. Moreover, the haplotype containing rs5758550 and rs16947 predict extensive CYP2D6 activity more accurately than CYP2D6*2A, a surrogate marker for extensive activity. Conclusion: With further studies, the results support possible incorporation of rs5758550 and rs16947 into CYP2D6 biomarker panels for more accurate prediction of CYP2D6 metabolizer status.